2015
DOI: 10.3390/rs70100725
|View full text |Cite
|
Sign up to set email alerts
|

Angular Dependency of Hyperspectral Measurements over Wheat Characterized by a Novel UAV Based Goniometer

Abstract: Abstract:In this study we present a hyperspectral flying goniometer system, based on a rotary-wing unmanned aerial vehicle (UAV) equipped with a spectrometer mounted on an active gimbal. We show that this approach may be used to collect multiangular hyperspectral data over vegetated environments. The pointing and positioning accuracy are assessed using structure from motion and vary from σ = 1° to 8° in pointing and σ = 0.7 to 0.8 m in positioning. We use a wheat dataset to investigate the influence of angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 48 publications
(53 reference statements)
0
86
0
1
Order By: Relevance
“…Depending on the capture mechanism, there are typically artefacts related to noninstantaneous (time delay) capture across bands, or physical offsets between bands [53]. There has also been interest in (nonimaging) UAS-mounted (hyperspectral) spectrometers [54].…”
Section: Sensorsmentioning
confidence: 99%
“…Depending on the capture mechanism, there are typically artefacts related to noninstantaneous (time delay) capture across bands, or physical offsets between bands [53]. There has also been interest in (nonimaging) UAS-mounted (hyperspectral) spectrometers [54].…”
Section: Sensorsmentioning
confidence: 99%
“…Using these technologies, spectral remote sensing measurements can be made cost-efficiently, with greater accuracy and detail than ever before. Several pushbroom hyperspectral imaging sensors [2][3][4][5][6] and point spectrometers [7,8] have recently been implemented in UAVs. Hyperspectral cameras based on the 2D frame format sensors have entered the market in recent years, offering an interesting alternative for hyperspectral data capture [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Grenzdörffer and Niemeyer [32] also used a consumer-grade camera mounted on a UAV to study the anisotropic reflectance behavior of winter wheat fields by capturing images at different view zenith and azimuth angles covering the full hemisphere. Burkart et al [33] used a hyperspectral UAV-based point spectrometer to collect multi-angular data of several vegetated areas and compared the measurements with the SCOPE model. Honkavaara et al [34] have demonstrated a method for extracting the reflectance anisotropy from multi/hyperspectral frame images in the georectification process.…”
Section: Introductionmentioning
confidence: 99%